Hydrodynamic analysis of human swimming based on VOF method - Zhan, J.-M.; Li, T.-Z.; Chen, X.-B.; Li, Y. S. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
A 3-D numerical model, based on the Navier-Strokes equations and the RNG k-e turbulence closure, for studying hydrodynamic drag on a swimmer with wave-making resistance taken into account is established. The volume of fluid method is employed to capture the undulation of the free surface. The simulation strategy is evaluated by comparison of the computed results with experimental data. The computed results are in good agreement with data from mannequin towing experiments. The effects of the swimmer`s head position and gliding depth on the drag force at different velocities are then investigated. It is found that keeping the head aligned with the body is the optimal posture in streamlined gliding. Also wave-making resistance is significant within 0.3 m depth from the free surface.